ETIKA DALAM KERJASAMA SENI DI TENGAH KONFLIK GLOBAL. KOLABORASI SENI DEWAN KESENIAN JAKARTA (DKJ) DAN UKRAINIAN INSTITUTE (UI) TAHUN 2024 - Ivana Noor; Agus Satory (INTELIGENSIA MEDIA, 2025)
The dynamics of international art cooperation in the contemporary globalization era present significant ethical challenges and complexities, particularly in the context of cultural diplomacy between art institutions from developing countries and nations experiencing geopolitical conflicts, such as the relationship between Jakarta Arts Council (DKJ) and Ukrainian Institute amid prolonged war conditions. This research aims to comprehensively analyze the application of ethical principles in bilateral art cooperation during year of 2024, identify ethical factors influencing decision-making, and formulate a sustainable international art corporation ethical model. In writing the research employs a qualitative approach with library research methodology, analyzing academic literature from 2021 – 2025 through thematic analysis techniques with applied ethics theoretical framework. This research successfully identified five fundamental ethical principles: humanitarian solidarity (35%), artistic integrity (25%), political neutrality (20%), transparency (15%) and accountability (5%). The main dilemma lies in the tension between humanitarian solidarity and political neutrality, resolved through intensive dialogue, third-party mediation, and contextual adaptation. The integrated ethical model combining care ethics with local cultural contexts proves effective in managing ethical conflicts, providing practical guidelines for Indonesian arts institutions in responsible and sustainable international cooperation.